Vaccinovigilance in Europe: need for timeliness, standardization and resources - Kari S. Lankinen; Satu Pastila; Terhi Kilpi; Hanna Nohynek; P. Helena Mäkelä; Patrick Olin (Bulletin of the World Health Organization, 2004)
OBJECTIVE: To identify gaps in the systems for reporting adverse events following immunization (AEFI) in Europe by means of an interactive database constructed using a standardized approach. METHODS: A comparative survey was conducted in 1999-2000, using structured questionnaires addressed to the government authorities responsible for national immunization programmes and drug safety surveillance in all European Union (EU) Member States and in Norway and Switzerland. FINDINGS: The reporting of adverse vaccine reactions (AVRs) is covered by regulations in 13 of the 17 countries. Four countries have a specialized expert group with responsibility for vaccine safety. Only six professionals work full-time on vaccine safety in the 17 countries; in four of these countries the person is medically qualified. Fourteen countries have centralized reporting systems; in 14 countries the responsible authority is the drug regulatory agency. AEFI are reported using the procedure used for adverse drug reactions (ADRs) in all except four countries. The reporting form is not usually designed for vaccines and important details may therefore not be requested. Clinical definitions for vaccine reactions are not available. Twelve countries have appropriate official definitions for events or reactions, but the list of reportable events varies considerably between countries. The assessment of adverse vaccine reactions (AVRs) is hampered by lack of exact denominator data. Feedback to the rapporteurs was provided in 13 countries, but its quality was highly variable. CONCLUSION: The database facilitated a simple comparison of vaccinovigilance systems across participating countries. Most of the problems identified related to the reporting and analysis of AEFI could be solved through standardization and intensified international collaboration. On a national level, functional vaccinovigilance systems should be the shared responsibility of the drug regulatory authority and the national immunization programme. The resources for development and management of vaccine safety systems should be urgently improved.